Internationalizing Quality Assessment in Central Asia - Merrill, Martha; Yakubova, Shakhnoza; Turlanbekova, Zhazira (International Higher Education, 2011)
Higher education institutions in Kyrgyzstan and Kazakhstan have started internationalizing quality assessment procedures; those in Turkmenistan, Uzbekistan, and Tajikistan have not. The differences concern politics (the willingness of national leadership to be transparent, internally and externally) and economics (the nation's ability to finance educational reform and to resist inappropriate "educational exports" of donor nations) more than educational quality. The plethora of processes in Kyrgyzstan reflects the priorities of donors; Kazakhstan is trying to balance national goals with Bologna standards.